SINTESIS BIODIESEL DARI FRAKSI MINYAK CPO (CRUDE PALM OIL) PARIT MELALUI ESTERIFIKASI DAN TRANSESTERIFIKASI TERKATALISIS ZrO2/SO3-H+ DAN KOH - , Idra Herlina, Prof. Dr. rer. nat. Karna Wijaya, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The catalyzed biodiesel synthesis from oil fraction of pond CPO was conducted. The research was performed in two steps: First, preparation of ZrO2/SO 3 -H + through wet impregnation of ZrOCl 2.8H 2 O of 1 g and 15 mL H 2SO4 of 0.5 M. Second, the synthesis of biodiesel which was done through 2 stages, i.e. esterification of oil fraction of pond CPO catalyzed by ZrO2/SO 3 -H + and transesterification which was catalyzed by KOH. The characterization result demonstrated that ZrO2/SO 3 -H + was successful synthesized from ZrOCl 2.8H 2O and H2SO4 confirmed by FT-IR and XRD analysis results. Meanwhile, the biodiesel could be synthesized via ZrO2/SO 3 -H + catalyzed esterification and KOH catalyzed transesterification with conversion of 68.96%. The excistence of biodiesel was proofed by the appearance of several peaks which was in agreement with the peak of methyl palmitate (48.51%), methyl oleate (46.38%), methyl stearate (3.84%), methyl myristate (0.97%), and methyl laurate (0.3%). Based on the ASTM data, the biodiesel was qualified as diesel fuel according to SNI-04-7182-2006